GENETIC DIVERSITY INVESTIGATION AND MOLECULAR MARKERS ESTABLISHMENT FOR IDENTIFICATION OF SEVERAL INITIALLY SELECTIVE AVOCADO (Persea americana Miller) STRAINS IN LAMDONG PROVINCE - Lê Ngọc Triệu (Tạp chí Khoa học Đại học Đà Lạt, 2017)
Morphologically and genetically investigation and estimation are necessary for train/cultivar identification and breeding in many crops. Materials from several selective avocado strains in Lamdong province were collected for genetic diversity analysis and strain identification. Initially morphological characteristics of fruit and yield data of 11 avocado strains were recorded to contribute to data establishment for strain identification data. DNA fingerprints recorded with 10 ISSR primers including 125 electrophoresis DNA band were used for genetic diversity estimation of 11 investigated strains set, in the result, the average expected heterozygosity (gene diversity) was He = h = 0.3072, Shannon index was I = 0.4608, and percentage of polymorphic bands was PPB = 91.84%. Also with the same 10 ISSR primers, DNA fingerprints recorded from 18 samples (3 samples per strain) including 98 electrophoresis DNA band were used for identification 06 investigated avocado strains. Based on the occurrence or absence of specific electrophoresis DNA band, 9 single ISSR markers and 25 double/multiple ISSR markers were established to identify these 6 strains. These initially achieved results provide the necessary data for avocado breeding and development in general and identification 6 potential avocado strains.